Hedging Spot Fuel Oil in Singapore: Will the New Simex Contract Succeed - Bailey, Warren (Institutional Knowledge at Singapore Management University, 1990)
We assess SIMEX's new market for fuel oil futures by examining its effectiveness in hedging a cash fuel oil position in Singapore. We find that the SIMEX contract can eliminate about two-thirds of the volatility of a Singapore cash position and is many times more effective than a cross-hedge constructed with overseas contracts. Given its potential usefulness as a hedging tool for the regional petroleum industry, we anticipate that the new contract will be a success.